Penerapan Model Pembelajaran Discovery Learning dengan Media Google Form untuk Meningkatkan Minat dan Hasil Belajar Siswa pada Mata Pelajaran Fiqih - Wajdi, Muh Barid NIzarudin; Rahmania, Nurani; Wibakti, Aji restu (IERA, Islamic Education and Research Academy, 2020)
This study aims to determine the effectiveness of applying the Discovery Learning model using Google Forms as a medium to improve students' interest and learning outcomes in the Fiqh subject of class XI MAPK at Al Hidayah in the academic year 2020/2021. The research method used is a pre-experimental design with a one-group pretest-posttest design. The sample of this study was students of class XI MAPK at Al Hidayah with a total of 35 students. Data collection techniques used were tests and questionnaires. The results of the study showed that the application of the Discovery Learning model using Google Forms as a medium can improve students' interest and learning outcomes in the Fiqh subject of class XI MAPK at Al Hidayah. This is evidenced by the increase in the average pretest score of 63.71 to an average posttest score of 84.86, and an increase in the average interest questionnaire score from 73.14 to 84.57. Thus, it can be concluded that the application of the Discovery Learning model using Google Forms as a medium is effective in improving students' interest and learning outcomes in the Fiqh subject of class XI MAPK at Al Hidayah in the academic year 2020/2021.